(3BOGH GdUMHI hGdoeYGTQI eY GdNGdb hGdeNdhbs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj YeQ Uahg YHGOg HdWGFa GdJNUjU WhdkG hEeJfGfkG hCda Hjf bdhHge s
(3BNQgG (B:s
(3hQLd ai Tc aj Gddg hGdbfhW ef QMeJg Je cJGH BOGH GdUMHI HMeO Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI HZOGO (B- (3GdOQGSGJ GdYdjG (B(1125) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs